A Non-Obligate Association Between the Red Alga, Boldia, and Pleurocerid Snails - R. Vincent Howard; Bruce C. Parker (Hello World!, 1981)
An unusual freshwater red alga, Boldia, inhabits certain streams of the Southern Appalachians often growing upon the shells of three species of pleurocerid snails. While this alga-snail association is not obligate in all habitats, evidence suggests a long-term evolution of a proiocooperative or commensalistic type bound to the seasonal reproductive cycles, development, and survival of the two organisms in simlar riffle habitats of Appalachian streams. The relatively high manganese content of both the snail periostracum and rocks to which Boldia was found attached, as well as other environmental features (i.e., photoperiod, water chemistry, and flow regime) suggest explanations for the habitat requirements and present distribution of this red alga. Boldia is an unusual freshwater red algal genus which frequently develops on the shells of three species of snails, Leptoxis (Mudalia) dilatata, L. cranata, and Oxytrema laqueata. During a three-year seasonal investigation of the systematics, distribution, and ecology of Boldia (Howard, 1977), the association of Boldia with various pleurocerid snails was often observed. While no obligate form of symbiosis was observed, it seemed unlikely that this polymorphic red alga would be able to maintain a population in streams without the snail association. Apparently, the alga-snail association is beneficial to one, if not both, organisms, and the association probably had a long evolutionary history within streams of the southern Appalachian Mountains.